To compute the distance between points B and C, we can use the distance formula, which is:
√((x2 - x1)^2 + (y2 - y1)^2)
In this case, the coordinates of point B are (-2, -6) and the coordinates of point C are (10, -1).
So the distance between points B and C is:
√((10 - (-2))^2 + (-1 - (-6))^2)
= √((10 + 2)^2 + (-1 + 6)^2)
= √(12^2 + 5^2)
= √(144 + 25)
= √169
= 13
Therefore, the distance between points B and C is 13.
Emaniee would like to build a ramp for her dog over some stairs. Compute the distance between points B and C
B (-2, -6)
C (10, -1)
1 answer